Rickety Stitch and the gelatinous goo - Costa, Ben, 1984-; Parks, James (Alfred A. Knopf, 2017)
Rickety is a minstrel skeleton who's somehow retained his soul. Along with a bag of squishy jelly named Goo, who only Rickety can understand, Rickety sets out on an adventure to discover his roots.